HIV, hepatitis B and C, and syphilis prevalence and coinfection among sex workers in Southern Brazil - Fabiana Schuelter-Trevisol; Geisiane Custódio; Ana Carolina Barreto da Silva; Mikely Byala de Oliveira; Audrei Wolfart; Daisson José Trevisol (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Introduction Sex workers (SWs) are vulnerable to HIV, hepatitis, and syphilis coinfection. Methods A cross-sectional study was conducted in Tubarão, Laguna, and Imbituba, Southern Brazil. We surveyed 147 SWs using face-to-face interviews and blood sampling for serological evaluation. Results Prevalence of hepatitis B (HBV) was 23.1%, syphilis 19.7%, hepatitis C (HCV) 8.8%, and HIV 8.8%. Of 13 HIV-infected patients, 3 were co-infected with HCV, 4 with syphilis, and 5 with HBV. Conclusions SWs had high HIV infection rates, and coinfection with viral hepatitis and syphilis.